Benefits of Chimeric Antigen Receptor T-Cell Therapy for B-Cell Lymphoma - Zhou, Wenyujing; Chen, Weihong; Wan, Xiaochun; Luo, Changru; Du, Xin; Li, Xiaoqing; Chen, Qian; Gao, Ruiwen; Zhang, Xiaohan; Xie, Mei; Wang, Mingjun (Frontiers in Genetics, 2022)
Objective: To study the benefits and risks of anti-CD19 chimeric antigen receptor (CAR) T-cells in adults with B-cell lymphoma. Methods: From October 2015 to October 2021, we treated 5 patients with B-cell lymphoma, including 2 mantle cell lymphomas 1 Burkitt lymphoma, 1 diffuse large B-cell lymphoma and 1 chronic lymphocytic leukemia/small lymphocytic lymphoma. Five days before the infusion of CAR T-cells, the patients were treated with FC regimen. The median of the total number of infusion CAR T-cells was 350*10^6 (88*10^6-585*10^6). Results: (1) Case 1~case 3 patients that received induction therapy of CAR T-cells obtained complete remission (CR) in the case 1 and case 3 and partial remission (PR) in case 2. ATM and D13S25 gene deletions of case 3 turned negative 42 days after CAR T-cell therapy, molecular biology CR (mCR) and minimal residual disease (MRD) is negative for 5 years and 6 months. The case 3 patient was cured. (2) The TP53 gene mutation of case 4 patient get negative on 1 month after CAR T-cell therapy. MRD negative after CAR T-cells therapy has been 41 and 42 months in the case 4 and case 5 respectively. (3) Case1~case 3 patients developed cytokine release syndrome (CRS) without encephalopathy syndrome and another serious adverse events, CRS can be well controlled by tocilizumab, etanercept, glucocorticoid, plasmapheresis. Conclusion: CAR T-cell therapy is beneficial to relapsed/refractory B-cell lymphoma, and the side effects of CAR T-cell therapy can be cured. CAR T-cell therapy has good efficacy and no side effects on MRD of B-cell lymphoma.